2007
DOI: 10.1680/stbu.2007.160.5.247
|View full text |Cite
|
Sign up to set email alerts
|

Catenary action in steel-framed buildings

Abstract: The current paper is of relevance to engineers engaged in the design of buildings in which severe column damage resulting from malicious actions is a design scenario. The tying force method as used for providing robustness to steel-framed buildings relies upon catenary action to redistribute loads following column damage. Fortunately severe column damage is extremely rare and for this reason it is not well understood if this load redistribution mechanism is reliable. The current paper presents results of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 5 publications
0
19
0
1
Order By: Relevance
“…Recent calculations of the factors of safety (Byfield and Paramasivam, 2007) illustrate that the codified procedure provides only a lower bound estimate of the tying force required to arrest the downwards movement of a damaged bay of the building as it ignores the dynamic amplification due to the additional force needed to absorb the kinetic energy. In addition, the inadequacy of rotational capacities of industry-standard connections to redistribute loads through catenary action in steelframed buildings has been highlighted (Byfield, 2004).…”
Section: Member Tyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent calculations of the factors of safety (Byfield and Paramasivam, 2007) illustrate that the codified procedure provides only a lower bound estimate of the tying force required to arrest the downwards movement of a damaged bay of the building as it ignores the dynamic amplification due to the additional force needed to absorb the kinetic energy. In addition, the inadequacy of rotational capacities of industry-standard connections to redistribute loads through catenary action in steelframed buildings has been highlighted (Byfield, 2004).…”
Section: Member Tyingmentioning
confidence: 99%
“…The connection axial load capacity is commonly obtained from direct tension tests (Owens and Moore, 1992), which do not include connection rotation and subsequent prying action, meaning that the predicted axial capacity may be significantly greater than in reality. This problem has been the subject of recent investigations (Byfield and Paramasivam, 2007) where results indicate that many simple connections possess insufficient ductility to accommodate the large rotations that occur during catenary action. For these scenarios a single rotational hinge, or yield element, which does not take account of axial loads is usually deemed unsuitable.…”
Section: The Modelling Of Connections During Progressive Collapse Anamentioning
confidence: 99%
“…However, since TFM does not consider the dynamic amplification of tying force, this approach is unable to prevent the progressive collapse in steel frame buildings if low ductility connections are used [12], thus limiting the development of full catenary action.…”
Section: Introductionmentioning
confidence: 99%
“…By general consensus however, its suitability as a measure of resistance to progressive collapse is somewhat doubtful [5]. Relevant studies [6][7][8][9][10] have demonstrated that tying alone does not account for all the mechanisms likely to be necessary to arrest collapse, while the connection deformations required in order to develop catenary action -i.e. the load carrying mechanism associated with tying -are often considerably greater than the available deformation capacities.…”
Section: Introductionmentioning
confidence: 99%